Desenvolvimento de modelo, para gestão de logística reversa de lixo eletroeletrônico, usando aplicativo web para redes de colaboração tecnológicas - Moreira, Sérgio Clério Jorge (2012)
Collaborative environments, whether internet-based (eg. social networks) or personal-based (eg. activities in schools), can produce relevant information to support reverse logistics of the so-called junk electronics. Although the Federal Law 12.305/2010, enacted in 2011, states that the manufacturers, importers, distributors, traders, governments and consumers of electronic products are responsible for the electronic waste disposal; there are no mechanisms to adequately meet the demand of the electronic waste production. This research deals with the integration of web-based collaborative environments, which are able to produce information of sufficient high quality and quantity to meet the interests of the federal and local governments and different corporations. In this study, some mechanisms that can minimize the impact of the electronic waste on the environment in the medium- and long-term have been identified. Moreover, some characteristics of the collaborative environments, the reverse logistics and the electronic waste have been also investigated. As a result, we have proposed a model that can facilitate the gathering of information coming from diffuse collaborative environments and that can structure such information (classify, categorize, order, map, etc.), with the purpose of making it available for the use in reverse logistics of the main stakeholders (governments and companies), according to the Federal Law 12.305/2010. The chosen strategy to conduct this study was the constructive research. Such strategy can be defined as a search procedure to produce innovative artifacts in order to solve different problems faced in the real world and, thereby, to make a contribution to the theory of the academic discipline in which the strategy is applied. The generated artifact in this research is a solution to properly manage the information from the collaborative environment (knowledge management) as a proof of concept of the proposed model.